2017
DOI: 10.1097/moh.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Rendering factor Xa zymogen-like as a therapeutic strategy to treat bleeding

Abstract: Purpose of review New therapies are needed to control bleeding in a range of clinical conditions. This review will discuss the biochemical properties of zymogen-like FXa, its pre-clinical assessment in different model systems, and future development prospects. Recent findings Underlying many procoagulant therapeutic approaches is the rapid generation of thrombin to promote robust clot formation. Clinically tested prohemostatic agents (e.g factor VIIa) can provide effective hemostasis to mitigate bleeding in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Recently, several long-acting FXa that was developed by changing the amino acid composition structure were used to clinical trial. The results showed that patients were highly tolerated and safe, and suppressed acute intracranial hemorrhage of patients [12,13] . These studies suggested that the treatment of hemophilia can also be achieved by intervening in the components of the "bypass" coagulation pathway.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several long-acting FXa that was developed by changing the amino acid composition structure were used to clinical trial. The results showed that patients were highly tolerated and safe, and suppressed acute intracranial hemorrhage of patients [12,13] . These studies suggested that the treatment of hemophilia can also be achieved by intervening in the components of the "bypass" coagulation pathway.…”
Section: Introductionmentioning
confidence: 95%
“…Enzymes catalyze all the fundamental transformations required to convert matter and energy into living systems. Society has benefited profusely from adaptation of pre-existing enzymes for industrial, research and medical uses [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, pre-existing enzymes are often not optimal for industrial applications due to temperature, pH and solvent stability, as well as substrate specificity and activity limitations [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%